2021
DOI: 10.3389/fendo.2021.681974
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Urinary Exosomal HSD11B2 mRNA Expression: A Useful Novel Tool for the Diagnostic Approach of Dysfunctional 11β-HSD2-Related Hypertension

Abstract: ObjectiveApparent mineralocorticoid excess (AME) is an autosomal recessive disorder caused by the 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) enzyme deficiency, traditionally assessed by measuring either the urinary cortisol metabolites ratio (tetrahydrocortisol+allotetrahydrocortisol/tetrahydrocortisone, THF+5αTHF/THE) or the urinary cortisol/cortisone (F/E) ratio. Exosomal mRNA is an emerging diagnostic tool due to its stability in body fluids and its biological regulatory function. It is unknown whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Heterozygous hypertensive subjects had higher concentrations of HSD11B2 mRNA transcripts than heterozygous normotensive subjects, suggesting a modulation of exosomal HSD11B2 mRNA associated with both mutation carrier status and hypertensive status. Interestingly, the F/E urinary ratio also correlated with the HSD11B2 mRNA copy number, thus validating the use of the F/E ratio as a possible useful surrogate marker of 11β-HSD2 enzyme activity ( 8 ).…”
Section: Approaching Endocrine Hypertension By the Analysis Of Mrna F...mentioning
confidence: 59%
See 1 more Smart Citation
“…Heterozygous hypertensive subjects had higher concentrations of HSD11B2 mRNA transcripts than heterozygous normotensive subjects, suggesting a modulation of exosomal HSD11B2 mRNA associated with both mutation carrier status and hypertensive status. Interestingly, the F/E urinary ratio also correlated with the HSD11B2 mRNA copy number, thus validating the use of the F/E ratio as a possible useful surrogate marker of 11β-HSD2 enzyme activity ( 8 ).…”
Section: Approaching Endocrine Hypertension By the Analysis Of Mrna F...mentioning
confidence: 59%
“…The results for HSD11B2 mRNA transcripts, on the other hand, were surprising, showing an opposite trend than expected based on genotypes. In fact, highest HSD11B2 gene expression (as measured by mRNA transcripts) was observed in 662C>G homozygous, with a decreasing trend for heterozygous and then for wild types ( 8 ).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, it is reported that the download expression of miRNA (miR‑192‑5p and miR‑204‑5p) in urinary exosomes also plays a potential role regulating the phenotype [ 68 ]. Santis et al identified that the expression level of exosomal urinary HSD11B2 mRNA was closely associated with the hypertension phenotype [ 69 ].…”
Section: Genetics Of Amementioning
confidence: 99%